(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2023)
The article talks about the importance of self-education in selfdevelopment. Self-education is understood as a conscious and purposeful activity aimed at discovering, validating and improving personal qualities, skills, behavior and interactions with the outside world.